Respiratory viruses in neonates: A prospective, community-based birth cohort study - Sarna, Mohinder; Alsaleh, A.; Lambert, S.; Ware, R.; Mhango, L.; Mackay, I.; Whiley, D.; Sloots, T.; Grimwood, K. (LIPPINCOTT WILLIAMS & WILKINS, 2016)
© 2016 Wolters Kluwer Health, Inc. All rights reserved. A community-based birth cohort study collected weekly nasal swabs and recorded daily symptoms from 157 full-term infants. An average of 0.25 (95% confidence interval: 0.18, 0.34) respiratory virus infections per neonatal period were detected. Human rhinoviruses of diverse subtypes dominated; almost 50% were asymptomatic and continued rhinovirus detections may signify new genotypes. Respiratory viruses are common and often unrecognized in healthy neonates.